Theoretical insights into the structural, spectroscopic, solvent effect, reactivity, NCI, and NLO analyses of 5,7-dichloro-8-hydroxyquinoline-2-carbaldehyde - Kucuk, Ceyhun (European Journal of Chemistry, 2025)
In this study, the characterization of the 5,7-dichloro-8-hydroxyquinoline-2-carbaldehyde molecule was carried out by nuclear magnetic resonance (1H and 13C NMR), Fourier transform infrared (FT-IR), ultraviolet-visible (UV-vis) spectroscopy and theoretical calculations in density functional theory (DFT) and time-dependent density functional theory (TD-DFT). The integral equation formalism polarizable continuum (IEFPCM) solvation model was used for ethanol, dimethylsulfoxide (DMSO), and water solvents. The conformation of the molecule was analyzed, and the most stable structure was optimized, and the geometry and electronic structure of the optimized structure were examined. The chemical stability and charge transport inside the molecule were validated by the computed HOMO-LUMO band gap energies. Characteristics such as non-linear optic properties (NLO), charge analysis, and molecular electrostatic potential (MEP) aid in determining the electrophilic/nucleophilic nature. Compound intermolecular interactions were investigated by topological studies, including noncovalent interaction (NCI), reduced density gradient (RDG), electron localization function (ELF), and localized orbital locator (LOL). The natural bond order (NBO) analysis was used to examine the changes between the hyperconjugative interaction energy E(2) and the electron densities of the donor (i) and acceptor (j) bonds. The interaction energy, the NCI study, and the NBO analysis revealed that the ligand becomes stronger in the presence of a pyridine ring.